Experimental investigation on suitability of carbon fibre thin plies for racquets - Bhudolia, S. K.; Perrotey, P.; Joshi, S. C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
In the world of fast-growing technology, switch from traditional wooden and metallic sports racquets to next generation powerful racquets is inevitable with the advent of carbon fibres, which offer benefits like increased strength, stiffness, impact, and efficient vibration and damping properties. The introduction of carbon fibres, however, comes with challenges of choosing a right matrix system that, in combination, provides the best solution without sacrificing performance. Non-crimp fabric thin C-Ply composites have the potential to suppress the micro cracks and delamination until the material`s ultimate strength. But still, their usage and the possible advantages they can offer in sports applications like tennis racquets, badminton racquets or table tennis bats and so on are yet to be explored. This article aims at exploring the niche benefits offered by thin C-Ply™ carbon fibres in combination with thermoset and thermoplastic matrices in sports applications, especially racquets. The composites comprised multi-axial reinforcement fabrics/non-crimp fabrics infused with a room-temperature cure epoxy or a thermoplastic resin having low mix viscosity (200 cps) suitable for vacuum-assisted resin infusion. The mechanical properties of carbon fibre thin C-Ply/(thermoplastic or thermoset) composites pivotal in racquets, like tensile and flexural stiffness and modulus, have been determined experimentally. Double cantilever beam Mode I tests are also carried out to determine the bonding strength between the plies and the matrix interface as most of the failures in sports equipment are accompanied by either bond failures or imperfections within the structure. The findings of testing of various specimens are presented and discussed.